A new holistic conceptual framework for green supply chain management performance assessment based on circular economy. (10th September 2018) - Kazancoglu, Yigit; Kazancoglu, Ipek; Sagnak, Muhittin
Abstract: In circular economy, the Green Supply Chain Management (GSCM) provides the resource optimization and it is seen as a solution to solve environmental problems and consumption patterns within the whole supply chain. The GSCM implementation and performance assessment is relatively important for survival in an ever-increasingly competitive environment. Within the circular economy context; companies that aim to improve GSCM must constantly monitor their performance. In order to integrate the circular economy concept into GSCM, it is required to achieve an optimal balance of environmental, economic, logistics, organizational, and marketing performance indicators. However, in the literature, these indicators were investigated separately in terms of GSCM performance assessment, therefore, to achieve this optimal balance, it is necessary to assess these different indicators. Within this context, the aim of this paper is to propose a new holistic conceptual GSCM performance assessment framework which integrates environmental, economic, logistics, operational, organizational and marketing performance. The framework has three-dimensional hierarchy which includes the main criteria, sub-criteria, and the measures for the GSCM performance assessment which have great significance to implement effective GSCM. Graphical abstract: Image Highlights: Proposed a framework for GSCM performance based on a circular economy. Holistic GSCM performance model included criteria, sub-criteria and measures. Revealed the different dimensions of GSCM. Proposed a systematic framework in order to assess GSCM performance. The inclusion of the marketing criterion in GSCM performance.